ANALISIS PENGARUH TENAGA KERJA DAN BELANJA PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI SULAWESI TENGGARA TAHUN 2016 - Dwi Yusrianti Yussamsuar; Zainuddin Saenong; Heppi Millia (Universitas Halu Oleo, 2018)
One of the success factors of a region's economic growth can be seen from the quality of human resources and the budget that can be spent by the region itself. In the current era of globalization, these conditions need to be assessed by linking the influence of labor and government spending on economic growth. This study aims to determine and analyze the influence of Labor and Government Expenditure on Regency/City Economic Growth in Southeast Sulawesi in 2016. The data used are secondary data, the method used in this study is the documentation method. The analysis used is multiple linear regression. The results of this study indicate that the labor variable has a significance probability value of 0.462> 0.05, which means that the workforce variable does not significantly affect the Regency / City Economic Growth in Southeast Sulawesi. Whereas for government expenditure has a probability value of 0.018<0.05, meaning that there is a significant effect of the variable government spending on Regency/ City Economic Growth in Southeast Sulawesi.